PENGARUH ETOS KERJA ISLAMI DAN GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN RUMAH MAKAN AYAM LEPAAS LHOKSEUMAWE - Harjoni Desky (State Institute of Islamic Studies (IAIN) Salatiga, 2014)
The purpose of this study is to analyze and explain the significant influence of Islamic work ethic with employee performance.This study uses a quantitative approach. The type of this research is exploratory research study. The samplingtechnique in this study using census method. The technique used for conducting this research through documentation, interviews, and questionnaires.This research was done by using the census of 65 employees eating spicy chicken in Lhokseumawe. Data were collected through questionnaires, interviews and documentation further processed using descriptive analysis and Path. The results of the analysis show that: (1) Islamic work ethic and a significant positive effect on employee performance, (2) transformational leadership style and a significant positive effect on employee performance.